Low-viscosity, wear-resistant and anti-corrosion composite coating on surface of screw and preparation method thereof

By combining the hard coating with an organic coating with low surface energy characteristics, the composite coating on the screw surface is prepared, which solves the problem of the screw being prone to failure in high temperature and high pressure environments, and significantly improves its wear resistance, corrosion resistance and adhesion resistance performance.

CN119433445APending Publication Date: 2025-02-14ZHOUSHAN INST OF CALIBRATION & TESTING FOR QUALITY & TECHNICAL SUPERVISION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411528219.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Screws are prone to failure in high temperature and high pressure environments, have short service life, and traditional surface strengthening technology cannot effectively improve their wear resistance, corrosion resistance and adhesion resistance.

Method used

A composite coating technology combining hard plating and organic coating with low surface energy characteristics is used to prepare screw surface composite coating by multi-arc ion plating and pulse magnetron sputtering composite deposition technology.

Benefits of technology

On the basis of maintaining the hardness of the coating, the coating is given low surface energy characteristics, reducing the mutual adhesion between the coating and the material, and significantly improving the wear and corrosion resistance of the screw.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433445A_ABST
    Figure CN119433445A_ABST
Patent Text Reader

Abstract

The invention discloses a low-viscosity, wear-resistant and anti-corrosion composite coating on the surface of a screw and a preparation method thereof.The composite coating comprises a hard plating layer and an organic coating from inside to outside, the hard plating layer is formed on the surface of a screw base material and is made of a hard alloy material, the hard alloy material is CrIrNiN, and the organic coating is made of a hard alloy material. The organic coating adopts polyimide of which the side chain is grafted with a siloxane group and an o-carborane group. The composite coating for the surface of the screw rod, which is composed of the hard coating and the organic coating, is prepared through a multi-arc ion plating and pulse magnetron sputtering composite deposition technology, so that the coating is endowed with the characteristic of low surface energy on the basis of keeping the hardness of the coating, the mutual adhesion performance between the coating and a material is reduced, and the service life of the coating is prolonged. And the wear resistance, corrosion resistance and other properties of the surface of the screw are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of screw surface coatings, and in particular to a low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw and a preparation method thereof. Background Art

[0002] The screw is one of the core components of plastic machinery such as extruders and injection molding machines, and its quality directly determines the production efficiency and product quality of a piece of equipment. However, the working environment of the screw is relatively harsh. It is often in a high temperature and high pressure environment of 200-300℃, and it is also subjected to large shear force and friction. The corrosion and adhesion of high temperature melt and additives are very easy to fail, and the service life is only 6-8 months. Especially with the development of the plastics industry, the expansion of application fields, the promotion of policies such as "banning plastics, limiting plastics", "double carbon action" and the enhancement of social environmental awareness, new materials such as degradable plastics, solvent-free high-viscosity resins, functional fillers or additives are increasingly used; the requirements for precision and functional diversification of products are getting higher and higher; the requirements for environmental protection, low-carbon energy saving in the production process are getting stronger and stronger; traditional plastic machines and screw technologies are backward and can no longer meet the diverse technical needs. Therefore, improving the wear resistance, corrosion resistance and anti-adhesion properties of the screw surface is of great significance to the research and development of intelligent, mechanically precise, large-scale high-end plastic machines, ensuring the quality of plastic products and improving productivity.

[0003] In order to improve the comprehensive performance of the screw, domestic and foreign scholars have developed many technologies. One is to use alloy materials with excellent performance to make the screw, but it will greatly increase the manufacturing cost; the other is to use surface strengthening technology to treat the surface of the screw, including traditional processes such as surface quenching, carburizing, and nitriding, and electroplating, thermal spraying, laser cladding, vapor deposition and other technologies to apply a covering layer with a thickness of several nanometers to several microns on the surface of the screw, generally a hard coating such as electroplating layer, carbide, nitride, etc., which only relies on hardness to improve the wear resistance and corrosion resistance of the screw surface, but does not consider the compatibility and adhesion performance between the screw and the material. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a low-viscosity, wear-resistant, and anti-corrosion composite coating on the surface of a screw and a preparation method thereof, which combines a hard coating with an organic coating with low surface energy characteristics, and can give the coating low surface energy characteristics while maintaining the hardness of the coating, thereby reducing the mutual adhesion between the coating and the material and improving the wear resistance and corrosion resistance of the screw surface.

[0005] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] In the first aspect, the present invention proposes a low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw, the key of which is that the composite coating includes a hard coating and an organic coating from the inside to the outside, the hard coating is formed on the surface of the screw substrate, and the organic coating adopts a polyimide with side chain grafted siloxane groups and ortho-carborane groups, and its molecular formula is:

[0007]

[0008] Wherein, R is an o-carborane group.

[0009] Furthermore, the hard coating is formed of a hard alloy material, and the hard alloy material is CrIrNiN.

[0010] Further, the molecular formula of the ortho-carborane group is:

[0011]

[0012] Furthermore, the glass transition temperature T of the organic coating is g The residual weight at 800°C in air atmosphere is not less than 95.8wt%.

[0013] In a second aspect, the present invention provides a method for preparing a low-viscosity, wear-resistant and corrosion-resistant composite coating on a screw surface as described in the first aspect, comprising the following steps:

[0014] Step 1, pretreatment of screw substrate;

[0015] Step 2, furnace loading: load the required target material and screw substrate into the corresponding position of the cavity with a clean and smooth inner wall and no dust particles attached;

[0016] Step 3, preparation of hard coating: using multi-arc ion plating technology to prepare the hard coating on the surface of the screw substrate;

[0017] Step 4, preparation of organic coating: using high-power pulsed magnetron sputtering technology to prepare the organic coating on the surface of the hard coating.

[0018] Furthermore, the screw substrate pretreatment in step 1 includes:

[0019] Surface grease removal process: Use anhydrous ethanol to ultrasonically clean the screw substrate for 10 minutes to remove surface grease;

[0020] Surface impurity removal process: Use dry ice to clean the screw substrate for 5 minutes to remove surface impurities.

[0021] Furthermore, the specific steps of preparing the hard coating in step 3 are as follows:

[0022] Step 3.1, evacuate the chamber, raise the temperature to 450°C, introduce argon gas until the pressure in the chamber is maintained at 0.8 Pa, turn on the substrate bias and etching arc source, and use argon plasma to etch and clean the surface of the screw substrate. The etching arc source current is 60A, and the bombardment etching is performed for 5 minutes at -200V, -400V and -600V bias respectively;

[0023] Step 3.2, increase the argon gas flow rate until the pressure in the chamber is maintained at 1.5 Pa, turn on the Cr target alone, and plate the Cr transition layer for 10 minutes at a target current of 50 A and a bias voltage of -30 V;

[0024] Step 3.3, the argon gas is changed to nitrogen gas, the pressure in the chamber is maintained at 2Pa, and the CrN coating is deposited. The plating time is 15min under the conditions of Cr target current 80A and bias voltage -100V;

[0025] Step 3.4, increase the nitrogen flow rate until the pressure in the chamber is maintained at 2.5 Pa, turn on the Cr target and the IrNi alloy target at the same time, and plate the CrIrNiN coating. The plating time is 90 min under the conditions of Cr target current 80 A, IrNi alloy target current 100 A, and bias voltage -100 V;

[0026] Step 3.5, change nitrogen to argon, maintain the pressure in the chamber at 1.5 Pa, turn on the substrate bias and intermittent etching arc source, use argon plasma to etch the surface of the CrIrNiN coating, the etching arc source current is 120A, and the bombardment etching is carried out for 10 minutes at -800V and -1000V bias respectively to form the hard coating.

[0027] Furthermore, during the etching, cleaning and plating process, the temperature in the chamber is 450° C. and the rotation speed of the sample stage is 3 r / min.

[0028] Furthermore, the mass ratio of Ir to Ni in the IrNi alloy target is 2:8.

[0029] Furthermore, the specific steps of preparing the organic coating in step 4 are as follows:

[0030] When the temperature in the chamber drops to 250°C, pulsed magnetron sputtering is performed;

[0031] During the pulsed magnetron sputtering process: the charging voltage of the organic coating target is 360V, the micropulse width is 750μm, the frequency is 75HZ, the weak ionization stage is 200μs, the strong ionization stage is 400μs, the micropulse opening in the strong ionization stage is 8μs, the duty cycle is 45%, the bias voltage is -60V, the intracavity pressure is 3MPa, and the deposition time is 30min.

[0032] The remarkable effects of the present invention are:

[0033] 1. The present invention combines a hard coating with an organic coating having low surface energy characteristics, and prepares a composite coating for the screw surface consisting of a hard coating and an organic coating through multi-arc ion plating and pulsed magnetron sputtering composite deposition technology. Not only does it give the coating low surface energy characteristics while maintaining the hardness of the coating, but it also reduces the mutual adhesion between the coating and the material, effectively improving the wear resistance and corrosion resistance of the screw surface.

[0034] 2. The present invention prepares a CrIrNiN multi-element coating by adding other elements to the CrN hard coating having the advantages of good wear resistance, strong corrosion resistance, and good ductility, wherein: Ni can prevent the columnar growth structure of the coating and refine the grains, thereby improving the mechanical properties and corrosion resistance of the coating, and also reducing the surface free energy of the coating; iridium (Ir), as an ultra-high temperature antioxidant material, not only has a high melting point and high hardness, but also has extremely strong stability and extremely low oxygen permeability at high temperatures, which can greatly improve the high temperature oxidation resistance of the coating.

[0035] 3. The organic coating in the present invention adopts a polyimide with side chain grafted siloxane groups and ortho-carborane groups, wherein: the distance between the organic substituents on the silicon atom of the siloxane group is large, the mutual force is weak, and the barrier for rotation around the Si-O bond is low, so that the siloxane chain is extremely flexible and easier to migrate to the surface, giving the coating excellent low surface energy characteristics, and the water contact angle is about 102.5°, which greatly reduces the adhesion of the material on the screw surface; ortho-carborane has a stable cage structure and strong electron adsorption characteristics, so it has a large volume steric effect and excellent thermal stability, and can form BH···π chemical bond interactions with the organic aromatic structure on the polyimide main chain, giving the coating extremely high high temperature resistance, which can meet the temperature requirements of most application environments of the screw. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the structure of the present invention;

[0037] Figure 2 is a flow chart of the method of the present invention;

[0038] Figure 3 This is the surface roughness test result diagram of the composite coating;

[0039] Figure 4 It is a three-dimensional ultra-depth microscopic morphology image of the composite coating. DETAILED DESCRIPTION

[0040] The specific implementation manner and working principle of the present invention are further described in detail below with reference to the accompanying drawings.

[0041] Embodiment 1:

[0042] like Figure 1 As shown, this embodiment proposes a low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of the screw, wherein the composite coating includes a hard coating 2 and an organic coating 3 from the inside to the outside, wherein the hard coating 2 is formed on the surface of the screw substrate 1, wherein the hard coating 2 is formed of a cemented carbide material, wherein the cemented carbide material is CrIrNiN, and the organic coating 3 is a polyimide with side-chain grafted siloxane groups and ortho-carborane groups, and the molecular formula thereof is:

[0043]

[0044] Wherein, R is an o-carborane group.

[0045] In this example, the molecular formula of the ortho-carborane group is:

[0046]

[0047] In this field, CrN is currently the most widely used hard coating, which has the advantages of good wear resistance, strong corrosion resistance, good ductility, etc., but due to its own low hardness, high friction coefficient, general high-temperature oxidation resistance and other problems, its application range is limited. Therefore, in order to effectively improve the comprehensive performance of the CrN coating, the embodiment of the present invention prepares a CrIrNiN multi-element coating by adding other elements. Among them, the addition of nickel (Ni) can prevent the columnar growth structure of the coating, refine the grains, thereby improving the mechanical properties and corrosion resistance of the coating, and also reduce the surface free energy of the coating; iridium (Ir), as an ultra-high temperature antioxidant material, not only has a high melting point and high hardness, but also has extremely strong stability and extremely low oxygen permeability at high temperatures, which can greatly improve the high-temperature oxidation resistance of the coating.

[0048] The organic coating 3 uses a polyimide with side-chain grafted siloxane groups and ortho-carborane groups, wherein the distance between the organic substituents on the silicon atom of the siloxane group is large, the mutual force is weak, and the barrier for rotation around the Si-O bond is low, making the siloxane chain extremely flexible and easier to migrate to the surface, giving the coating excellent low surface energy properties, and the water contact angle is about 102.5°, which greatly reduces the adhesion of the material on the screw surface; ortho-carborane has a stable cage structure and strong electron adsorption properties, so it has a large volume steric effect and excellent thermal stability, and can form BH···π chemical bond interactions with the organic aromatic structure on the polyimide main chain, giving the coating extremely high high temperature resistance, and the glass transition temperature T g It is about 560℃, and the residual weight at 800℃ in air atmosphere exceeds 95.8wt%, which meets the temperature requirements of most application environments of the screw.

[0049] Embodiment 2:

[0050] like Figure 2As shown, the present invention proposes a method for preparing a low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw as described in Example 1, comprising the following steps:

[0051] Step 1, pretreatment of the screw substrate 1;

[0052] In this example, the pretreatment of the screw substrate 1 includes:

[0053] Surface grease removal process: Use anhydrous ethanol to ultrasonically clean the screw substrate 1 for 10 minutes to remove the surface grease;

[0054] Surface impurity removal process: Use dry ice to clean the screw substrate 1 for 5 minutes to remove surface impurities.

[0055] Step 2, furnace loading: load the required target material and screw substrate 1 into the corresponding position of the cavity with a clean and smooth inner wall and no dust particles attached;

[0056] Step 3: Preparation of hard coating 2:

[0057] In this embodiment, the multi-arc ion plating technology is used to prepare the hard coating 2 on the surface of the screw substrate 1. The specific steps are as follows:

[0058] Step 3.1: Evacuate the chamber to 5×10 -5 mbar, and the temperature is raised to 450°C, argon gas (purity not less than 99.9%) is introduced until the pressure in the chamber is maintained at 0.8Pa, the substrate bias and etching arc source are turned on, and the surface of the screw substrate 1 is etched and cleaned with argon plasma to enhance the bonding force between the coating and the substrate. The etching arc source current is 60A, and the bombardment etching is performed for 5 minutes at -200V, -400V and -600V bias respectively;

[0059] Step 3.2, increase the argon gas flow rate until the pressure in the chamber is maintained at 1.5 Pa, turn on the Cr target alone, and plate the Cr transition layer for 10 minutes at a target current of 50 A and a bias voltage of -30 V;

[0060] Step 3.3, the argon gas is changed to nitrogen gas (purity not less than 99.9%), the pressure in the chamber is maintained at 2Pa, and the CrN coating is deposited. The plating time is 15min under the conditions of Cr target current 80A and bias voltage -100V;

[0061] Step 3.4, increase the nitrogen flow rate until the pressure in the chamber is maintained at 2.5 Pa, turn on the Cr target and the IrNi alloy target at the same time, the mass ratio of Ir to Ni in the IrNi alloy target is 2:8, and plate the CrIrNiN coating. The plating time is 90 min under the conditions of Cr target current 80 A, IrNi alloy target current 100 A, and bias voltage -100 V;

[0062] Step 3.5, change nitrogen to argon, maintain the gas pressure in the chamber at 1.5 Pa, turn on the substrate bias and intermittent etching arc source, use argon plasma to etch the surface of the CrIrNiN coating to form "honeycomb" micro-nano structure pits, the etching arc source current is 120A, and the bombardment etching is carried out for 10 minutes at -800V and -1000V bias respectively to form the hard coating 2.

[0063] During the etching, cleaning and plating process, the temperature in the chamber is 450°C and the rotation speed of the sample stage is 3r / min.

[0064] Step 4: Preparation of organic coating 3:

[0065] This embodiment adopts high-power pulsed magnetron sputtering technology to prepare the organic coating 3 on the surface of the hard coating 2, and the specific steps are as follows:

[0066] When the temperature in the chamber drops to 250°C, the equipment is adjusted to high-power pulsed magnetron sputtering mode to perform pulsed magnetron sputtering;

[0067] During the pulsed magnetron sputtering process: the charging voltage of the organic coating 3 targets is 360V, the micropulse width is 750μm, the frequency is 75HZ, the weak ionization stage is 200μs, the strong ionization stage is 400μs, the micropulse opening time in the strong ionization stage is 8μs, the duty cycle is 45%, the bias voltage is -60V, the pressure in the cavity is 3MPa, and the deposition time is 30min, which is just enough to fill the "honeycomb" micro-nano structure pits on the surface of the CrIrNiN coating.

[0068] Finally, this embodiment also performs a performance test on the prepared composite coating, and the test results are as follows:

[0069] (1) Average hardness of composite coating: 1750.00HV;

[0070] (2) Three-dimensional ultra-depth microscopic morphology of composite coating:

[0071] from Figure 3 It can be seen that the composite coating is very dense and complete, and the surface roughness is very small, with the maximum difference being only about 2.01μm;

[0072] from Figure 4 It can be seen that the layer structure basically meets the design requirements, and the organic coating 3 with low surface energy characteristics fills the "honeycomb"-shaped micro-nanostructure pits on the surface more evenly, realizing the organic combination of the hardness of the CrIrNiN coating and the low surface energy characteristics of the organic coating 3.

[0073] (3) Average hardness water contact angle of composite coating: 100°.

[0074] In summary, the present invention combines a hard coating 2 with an organic coating 3 having low surface energy characteristics, and prepares a composite coating for the screw surface composed of a hard coating 2 and an organic coating 3 through multi-arc ion plating and pulsed magnetron sputtering composite deposition technology. Not only does it give the coating low surface energy characteristics while maintaining the hardness of the coating, but it also reduces the mutual adhesion between the coating and the material, thereby effectively improving the wear resistance, corrosion resistance and other properties of the screw surface.

[0075] The technical solution provided by the present invention is described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw, characterized by: The composite coating includes a hard coating and an organic coating from the inside to the outside. The hard coating is formed on the surface of the screw substrate. The organic coating adopts a polyimide with a side chain grafted siloxane group and an ortho-carborane group, and its molecular formula is: Wherein, R is an o-carborane group.

2. The low-viscosity, wear-resistant and corrosion-resistant composite coating on the screw surface according to claim 1 is characterized by: The hard plating layer is formed of a hard alloy material, and the hard alloy material is CrIrNiN.

3. The low-viscosity, wear-resistant and corrosion-resistant composite coating on the screw surface according to claim 1 is characterized in that: The molecular formula of the ortho-carborane group is:

4. The low-viscosity, wear-resistant and corrosion-resistant composite coating on the screw surface according to claim 1 is characterized by: The glass transition temperature T of the organic coating g The residual weight at 800°C in air atmosphere is not less than 95.8wt%.

5. A method for preparing a low-viscosity, wear-resistant and corrosion-resistant composite coating on a screw surface as claimed in any one of claims 1 to 4, characterized in that: The steps include: Step 1, pretreatment of screw substrate; Step 2, furnace loading: load the required target material and screw substrate into the corresponding position of the cavity with a clean and smooth inner wall and no dust particles attached; Step 3, preparation of hard coating: using multi-arc ion plating technology to prepare the hard coating on the surface of the screw substrate; Step 4, preparation of organic coating: using high-power pulsed magnetron sputtering technology to prepare the organic coating on the surface of the hard coating.

6. The method for preparing the low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw according to claim 5, characterized in that: The screw substrate pretreatment in step 1 includes: Surface grease removal process: Use anhydrous ethanol to ultrasonically clean the screw substrate for 10 minutes to remove surface grease; Surface impurity removal process: Use dry ice to clean the screw substrate for 5 minutes to remove surface impurities.

7. The method for preparing the low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw according to claim 5, characterized in that: The specific steps of preparing the hard coating in step 3 are as follows: Step 3.1, evacuate the chamber, raise the temperature to 450°C, introduce argon gas until the pressure in the chamber is maintained at 0.8 Pa, turn on the substrate bias and etching arc source, and use argon plasma to etch and clean the surface of the screw substrate. The etching arc source current is 60A, and the bombardment etching is performed for 5 minutes at -200V, -400V and -600V bias respectively; Step 3.2, increase the argon gas flow rate until the pressure in the chamber is maintained at 1.5 Pa, turn on the Cr target alone, and plate the Cr transition layer for 10 minutes at a target current of 50 A and a bias voltage of -30 V; Step 3.3, the argon gas is changed to nitrogen gas, the pressure in the chamber is maintained at 2Pa, and the CrN coating is deposited. The plating time is 15min under the conditions of Cr target current 80A and bias voltage -100V; Step 3.4, increase the nitrogen flow rate until the pressure in the chamber is maintained at 2.5 Pa, turn on the Cr target and the IrNi alloy target at the same time, and plate the CrIrNiN coating. The plating time is 90 min under the conditions of Cr target current 80 A, IrNi alloy target current 100 A, and bias voltage -100 V; Step 3.5, change nitrogen to argon, maintain the pressure in the chamber at 1.5 Pa, turn on the substrate bias and intermittent etching arc source, and use argon plasma to etch the surface of the CrIrNiN coating. The etching arc source current is 120A, and the bombardment etching is carried out for 10 minutes at -800V and -1000V bias respectively to form the hard coating.

8. The method for preparing the low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw according to claim 7, characterized in that: During the etching, cleaning and plating process, the temperature in the chamber is 450°C and the rotation speed of the sample stage is 3r / min.

9. The method for preparing the low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw according to claim 7, characterized in that: The mass ratio of Ir to Ni in the IrNi alloy target is 2:

8.

10. The method for preparing the low-viscosity, wear-resistant and corrosion-resistant composite coating on the surface of a screw according to claim 5, characterized in that: The specific steps of preparing the organic coating in step 4 are as follows: When the temperature in the chamber drops to 250°C, pulsed magnetron sputtering is performed; During the pulsed magnetron sputtering process: the charging voltage of the organic coating target is 360V, the micropulse width is 750μm, the frequency is 75HZ, the weak ionization stage is 200μs, the strong ionization stage is 400μs, the micropulse opening in the strong ionization stage is 8μs, the duty cycle is 45%, the bias voltage is -60V, the intracavity pressure is 3MPa, and the deposition time is 30min.